GENDER TEŃLIGI KRITERIYLARÍNÍŃ SOCIALLÍQ-MÁDENIY DETERMINANTLARÍ - Seitova, Z.P. (SCIENCE and SOCIETY, 2026)
This article analyzes gender equality criteria and their sociocultural determinants. It examines the influence of family, educational environment, and media space on the formation of gender identity and the reinforcement of stereotypes. The role of interaction between biological and social factors in determining behavior and social roles is emphasized. The article concludes that a comprehensive approach is necessary to create conditions for the equal development of individuals and to establish a sustainable model of gender equality.